Insulin-Like Growth Factor Regulates Peak Bone Mineral Density in Mice by Both Growth Hormone-Dependent and -Independent Mechanisms - Mohan, Subburaman (2003)
To evaluate the relative contribution of the GH/IGF axis to the development of peak bone mineral density (BMD), we measured skeletal changes in IGF-I knockout (KO), IGF-II KO, and GH-deficient lit/lit mice and their corresponding control mice at d 23 (prepubertal), 31 (pubertal), and 56 (postpubertal) in the entire femur by dual energy x-ray absorptiometry and in the mid-diaphysis by peripheral quantitative computed tomography. Lack of growth factors resulted in different degrees of failure of skeletal growth depending on the growth period and the growth factor involved. At d 23, femoral length, size, and BMD were reduced by 25–40%, 15–17%, and 8–10%, respectively, in mice deficient in IGF-I, IGF-II, and GH compared with the control mice. During puberty, BMD increased by 40% in control mice and by 15% in IGF-II KO and GH-deficient mice, whereas it did not increase in the IGF-I KO mice. Disruption of IGF-I, but not IGF-II, completely prevented the periosteal expansion that occurs during puberty, whereas it was reduced by 50% in GH-deficient mice. At d 56, femoral length, size, and BMD were reduced by 40–55%, 11–18%, and 25–32%, respectively, in mice deficient in IGF-I, IGF-II, and GH compared with the control mice. Our data demonstrate that: 1) mice deficient in IGF-I exhibit a greater impairment in bone accretion than mice deficient in IGF-II or GH; 2) GH/IGF-I, but not IGF-II, is critical for puberty-induced bone growth; and 3) IGF-I effects on bone accretion during prepuberty are mediated predominantly via mechanisms independent of GH, whereas during puberty they are mediated via both GH-dependent and GH-independent mechanisms.